2023
DOI: 10.1111/jar.13070
|View full text |Cite
|
Sign up to set email alerts
|

Staff perceptions following a training programme about reducing psychotropic medication use in adults with intellectual disability: The need for a realistic professional practice framework

Abstract: BackgroundThis redlined PDF shows all copy edited changes made to your manuscript. They are for your reference only. Please make all edits in the HTML version of the proofs. 2Adults with intellectual disability are at higher risk of being administered psychotropic medications. The SPECTROM training programme educates disability support workers on psychotropic medications and alternatives to these medications. MethodInterviews were conducted with 10 participants who took part in the pilot SPECTROM training prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Training is a responsibility carried out jointly between employees and the organization, where employees must design and attend training to develop their abilities so that they are wide open for better career paths for employees in the future. Training is an activity to improve one's employability with economic activity (Badhwar et al, 2023;Bao et al, 2023;Barratt et al, 2023). Meanwhile, employees who are motivated to carry out their work have the assumption that their task is a challenge that must be solved.…”
Section: Source: Results Of Research Data Processing 2023mentioning
confidence: 99%
See 1 more Smart Citation
“…Training is a responsibility carried out jointly between employees and the organization, where employees must design and attend training to develop their abilities so that they are wide open for better career paths for employees in the future. Training is an activity to improve one's employability with economic activity (Badhwar et al, 2023;Bao et al, 2023;Barratt et al, 2023). Meanwhile, employees who are motivated to carry out their work have the assumption that their task is a challenge that must be solved.…”
Section: Source: Results Of Research Data Processing 2023mentioning
confidence: 99%
“…Training is an activity to improve one's employability concerning economic activity (Badhwar et al, 2023;Bao et al, 2023;Barratt et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To address the issue of caregiver training, we have recently developed an online training resource backed up by face-toface workshops (SPECTROM; https://spectrom.wixsite.com/project) to help rationalise antipsychotics and other psychotropic medications (Deb et al, 2020). Two small pre, and post-intervention pilot studies of SPECTROM training in the United Kingdom (Deb et al, 2021) and Australia (Barratt et al, 2023;Wilson et al, 2022Wilson et al, , 2023 have received good feedback from the trainees and the trainers on the acceptability, practicality, applicability and relevance of SPECTROM to their practice and helped to empower support staff by increasing their knowledge of psychotropic medication and improving attitude toward using medication for challenging behaviour. Some participants in the current study found input from local pharmacists and nurse prescribers helpful in implementing STOMP.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also had an opportunity to provide qualitative interview data after the completion of the training, which has been reported elsewhere (Barratt et al . 2023).…”
Section: Methodsmentioning
confidence: 99%
“…All post-training surveys were sent via email by the research assistant, with a single repeat invitation to complete the survey. Participants also had an opportunity to provide qualitative interview data after the completion of the training, which has been reported elsewhere (Barratt et al 2023).…”
Section: Data Collectionmentioning
confidence: 99%